2013
DOI: 10.1039/c2dt32709k
|View full text |Cite
|
Sign up to set email alerts
|

The DNA binding site specificity and antiproliferative property of ternary Pt(ii) and Zn(ii) complexes of phenanthroline and N,N′-ethylenediaminediacetic acid

Abstract: The binding site specificity of the ternary complexes, [M(II)(phen)(edda)] (M(II) = Pt(2+) and Zn(2+); phen = 1,10-phenanthroline; edda = N,N'-ethylenediaminediacetic acid), for the self-complementary oligonucleotides (ODNs), ds(C(1)G(2)C(3)G(4)A(5)A(6)T(7)T(8)C(9)G(10)C(11)G(12))(2) (ODN1) and ds(C(1)G(2)C(3)G(4)T(5)A(6)T(7)A(8)C(9)G(10)C(11)G(12))(2) (ODN2), was studied by NMR measurements. The results indicated that [Pt(ii)(phen)(edda)] was partially intercalated between C(3)/G(10) and G(4)/C(9) base pairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…74 Similar result was shown by Nakamura et al with [Zn(II) (phen) (edda)] and suggested a weak intercalation mode. 75 In our studies we found that moderate increase in intensity of both band of CT-DNA and the moderate decrease in the ellipticity of the bands, particularly the long wavelength band of poly(I)poly(C) has been correlated to the function of both helix winding angle and base pair twist which may indicate a weak intercalation mode. These results show good agreement with EB displacement study.…”
Section: Characterization Of the Zinc Complex In Solutionmentioning
confidence: 50%
“…74 Similar result was shown by Nakamura et al with [Zn(II) (phen) (edda)] and suggested a weak intercalation mode. 75 In our studies we found that moderate increase in intensity of both band of CT-DNA and the moderate decrease in the ellipticity of the bands, particularly the long wavelength band of poly(I)poly(C) has been correlated to the function of both helix winding angle and base pair twist which may indicate a weak intercalation mode. These results show good agreement with EB displacement study.…”
Section: Characterization Of the Zinc Complex In Solutionmentioning
confidence: 50%
“…Despite the variety of physiological roles of the Zn(II) ion [11][12][13] and the wide repertoire of Zn(II) complexes utilized in many fields (binder complexes at DNA sites, [14][15][16][17] radioprotective agents, 18 tumor photosensitizers, 19 antidiabetic/insulinmimetic 20,21 and antibacterial or antimicrobic activities [22][23][24] ) only very recently wide interest is growing in the use of Zn(II) coordination complexes with low toxicity and low side effects in medicinal therapeutic applications, 25 for treating diabetes mellitus 26 or cancer. [27][28][29][30][31][32][33][34] Differently from zinc, copper, an essential microelement found in all living organisms, shows the unique ability to adopt two different oxidation states (Cu(II) and Cu(I)), giving rise, in metal complexes, to versatile coordination states and geometries. Due to the permeability of cancer cell membranes to copper compounds, a number of copper complexes have been screened for their anticancer activity and some of them were found to be active both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In this context, due to the physiological roles of zinc in cells and organs, a large interest is growing in the use of Zn(II) coordination complexes with low toxicity and low side effects in medicinal therapeutic applications, 8 for treating diabetes mellitus 9 or cancer. [10][11][12][13][14][15][16][17] In this context we have recently proposed low cost Zn(II) complexes with promising cytotoxic activity against different human cancer cells, focusing on pentacoordinated Zn(II) complexes whose coordination sphere is filled by a potentially intercalating N,N ligand and one or two O,O chelating bioactive ligands. 12,16 Substantial results have been obtained for this class of compounds in the case of the curcumin (curc, 1,7-bis-(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) derivative of the 4,4′-dinonyl-2,2′-bipyridine, complex A shown in Fig.…”
Section: Introductionmentioning
confidence: 99%